PENGARUH PENAMBAHAN EKSTRAK DAUN SIRSAK (Annona muricata L.)TERHADAP PROFIL FARMAKOKINETIKA PIROKSIKAM - Raharjo, Setyo Tri; Pambudi, Dwi Bagus; Mugiyanto, Eko (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
Piroxicam is one of the NSAID drug that common used in inflammation. Utilizing of herbal medicine along with synthetic drugs can lead to certain interactions, especially the occurrence of pharmacokinetic drug profile changes. The aim of this study is to determine the effect of addition of soursop leaf extract againt pharmacokinetic piroxicam profile. The method used was cross sectional using 6 rabbits, the data were analyzed statistically with t-test using SPSS version 21 program. The results showed that the piroxicam treatment had Cmax = 0.650 ?g / ml, tmax = 3 hours, t ½ = 0.693 hours, and AUC = 0.597 hours.?g / ml, while on treatment of combination of piroksikam with soursop leaf extract have value of Cmax = 0,683 ?g / ml, tmax = 1 hour, t ½ = 0,693 hours, and AUC = 0,652 jam.?g / ml. The result of data analysis using T test showed that there was significant difference in AUC value (p <0,05). These results suggest that the addition of soursop leaf extract may affect the piroxicam pharmacokinetic profile.